Aplicação de jogo lúdico para o ensino de ciências: jogo LUDOVID sobre a COVID-19 - Dias, Aniele Beatriz (Universidade Federal de São Carlos, 2023)
The present project proposed the elaboration and application of the LUDOVID game, based on the ludo game, the elaboration and implementation of a pedagogical proposal that addresses the problem of the COVID-19 pandemic with concepts of health and science correlated with topics of natural science (biology and chemistry) in an interdisciplinary way. The choice of the theme “COVID-19 pandemic” was determined after a bibliographical survey that demonstrated the lack of studies on the relationship of educational ludic games with the proposed theme, due to the fact that it is a recent topic. Another factor that influenced the choice was the spread of false news, the so-called “fake news”, released during the pandemic, stimulated by government policies that denied science. LUDOVID was applied in the Chemistry discipline offered to the high school students at Centro Educacional Avicenna LTDA, located in the cities of Leme/SP and Pirassununga/SP. This work sought to understand the playful pedagogical potential of the proposed game, in addition to identifying the factors that would indicate its effectiveness in relation to the understanding of the subjects that were taught during the class. In order to verify the applicability of this methodology for science teaching, the framework Messeder Neto (2016) and Savi (2011) was used. It was also possible to evaluate the students' perception in relation to their motivation, experience of playing a ludic game during a class and the impact of the game on their learning. Teachers who used the LUDOVID game proposal were also evaluated through a semi-structured interview, which was later evaluated by a descriptive analysis. They were also provided with a preliminary lesson plan that was prepared to help them in this activity, and were able to modify it according to their needs and perceptions in class. To evaluate the students' perception of the game, a questionnaire was used, the data collected was later analyzed as described by Savi (2011).
Ludic game application for science teaching: LUDOVID game about COVID-19
Keywords: Jogo lúdico; Ensino de ciências; Jogo Ludo; COVID-19; Ludic game; Science teaching; Ludo game; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::AVALIACAO DA APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO